Multimodality of Make Over Power Stay Advertisement - Lestari, Widya; Sinar, Silvana (RADIANT: Journal of Applied, Social, and Education Studies, 2022)
This research entitled "Multimodality of Make Over Power Stay Advertisement" is a multimodal research which contains interactions between verbal and visual semiotic modes to find the generic structure and the intent of the advertisement image. The purpose of this study is to identify potential generic structures in the advertisement image of 'Make Over Power Stay' and this thesis is prepared using a qualitative descriptive method to describe hidden meanings that are displayed in verbal and visual elements. In this thesis, the object that the writer analyzes is "Make Over Power Stay" advertisement. The data collection instrument in this thesis is selecting, focusing, simplifying, and abstracting empirical data. This analysis focuses on the Generic Structure Potential concept by (Cheong, 2004)in analyzing verbal and visual texts. The results of the analysis of the verbal text used in the ad advertisement are Announcements and the visual element most commonly used in the advertisement is the Lead.